UPAYA HUKUM KEBERATAN ATAS PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM KASUS PENARIKAN UNIT KENDARAAN MELALUI PIHAK EKSTERNAL (DEBT COLLECTOR) (Studi Putusan Nomor 03/PTS/BPSK/2020/PN.Padang dan Putusan Nomor 07/PDT/BPSK/2020/PN.Padang) - Bustanul Alamsyah (UNES Law Review, 2021)
Broadly speaking, BPSK decisions should be viewed as decisions that have permanent legal force. However, when compared to the principle (res judicata pro vitatate habetur) with Article 56 Paragraph (2) of the UUPK, it turns out that the parties can still file an objection to the District Court. The incident was caused by the weak position and authority given by UUPK to BPSK, especially regarding decisions that are final and binding. One of the factors that cause objections to the decision of the dispute settlement agency outside the court is in determining the type of dispute resolution that will be taken by the parties. The objection is that the settlement of the case should be resolved through BANI or the PN, but in this case the dispute resolution is resolved at BPSK. Based on the number of cases that have been resolved by the Padang City BPSK and the number of cases decided by the Padang City BPSK, it continues to the Padang Class IA District Court, starting from 2018 as many as 15 cases, in 2019 as many as 26 cases, then in 2020 as many as 61 cases. This shows an increase. Meanwhile, the number of cases decided by the Padang City BPSK continued to the Padang Class IA District Court, from 2018 there were 14 cases, in 2019 there were 3 cases, in 2020 there were 3 cases. This shows a decline. Based on the research and discussion, it can be seen that: First, the mechanism for objecting to the BPSK decision in the Class IA Padang District Court can be carried out if one of the litigants considers that the BPSK decision is unsuccessful so that they can file an objection to the Class IA Padang District Court with a note that after fulfilling the requirements the objection applicant may file an objection and the submission of the objection is still within the specified grace period, namely 14 (fourteen) days from the announcement of the BPSK decision and if the District Court accepts the objection, a decision will be given within 21 (twenty one) days at the latest. Second, the analysis of the judge's decision Number 03/PTS/BPSK/2020/PN.Padang and the judge's decision Number 07/PDT/BPSK/ 2020/ PN.Padang which was previously processed at BPSK Padang City, is an objection to the arbitration decision entered in The PN Padang Class IA cannot be said to be a new lawsuit or an appeal, the objection is a legal remedy taken specifically to object to the arbitration decision of the consumer dispute settlement body out of court.